Bioactivities of Digera muricata (L.) Mart. Available in Bangladesh - Miah, Mohammad Mohasin; Das, Pritom; Mridha, Shakil Ahammad; Kuddus, Md Ruhul; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Abstract not available Dhaka Univ. J. Pharm. Sci. 16(2): 251-254, 2017 (December)